2022
DOI: 10.29303/jppipa.v8i4.1660
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Virtual Lab in Science-Physics Learning Based on the STEM Approach

Abstract: Learning innovation in the laboratory has experienced very rapid development in the current era of technological development. One of these innovations is through the use of virtual laboratory classes in science learning, as is the case with temperature and heat materials. The aims of this research are to develop a virtual lab based on the STEM approach on the concepts of temperature and heat, to test the validity and practicality of virtual lab products based on the STEM approach. The development method used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…This finding aligns with research by Hidayat & Utomo (2015), who reported that the virtual laboratory they developed received 93%, so it was very practical. Rahmi et al (2022) also reported that the virtual lab in science-physics learning based on the STEM approach they developed was very practical based on acquiring a 96% practicality percentage in the student response trial.…”
Section: Figure 2 Display Of the Stem-based Virtual Laboratory Produc...mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding aligns with research by Hidayat & Utomo (2015), who reported that the virtual laboratory they developed received 93%, so it was very practical. Rahmi et al (2022) also reported that the virtual lab in science-physics learning based on the STEM approach they developed was very practical based on acquiring a 96% practicality percentage in the student response trial.…”
Section: Figure 2 Display Of the Stem-based Virtual Laboratory Produc...mentioning
confidence: 99%
“…Various virtual laboratories have been successfully developed by previous researchers in science subjects in junior high schools (Purwanti, Habibah, & Supriyanto, 2014;Nurhayati & Rohman, 2015;Ismail, Permanasari, & Setiawan, 2016;Adita & Julianto, 2016;Widowati, Nurohman, & Setyowarno, 2017;Sholikhah, Widowati, & Wibowo, 2017;Utami, Widowati, & Wibowo, 2017;Sabrinah, Tulenan, & Sompie, 2021;Herunata, Fadilah, & Affriyenni, 2022;Syukri, Rahmi, Saminan, Subramaniam, Artika, Huda, & Khaldun, 2022;Noris, Saputro, & Muzazzinah, 2022;Rahmi, Saminan, Syukri, Yusrizal, Khaldun, Artika, & Huda, 2022;Revanza, Ridlo, & Rizqi, 2023). However, only some STEM-based virtual laboratories on global warming topics for junior high school students have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…One form of utilization of computer technology in physics learning is the development of a VL (Billah & Widiyatmoko, 2018;Fadhilah et al, 2021;Masril et al, 2018;Rahmi et al, 2022). A virtual laboratory is defined as a form of interactive multimedia object.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, integrated modern VL research (Budai & Kuczmann, 2018). Meanwhile, VL research in the field of science, especially physics, is still limited to the STEM approach (Rahmi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%